Differential dissolution susceptibility of Paleocene foraminiferal assemblage from Farafra Oasis, Egypt. (January 2016) - Orabi, Orabi H.; Zaky, Amr S.
Abstract: Four inferred carbonate dissolution intervals are recognized at North Gunna section within the Dakhla and Esna formations (Paleocene) of the Farafra Oasis of Egypt as the following: 1) at the Danian/Selandian boundary (P3a/P3b), 2) at the upper part of Acarinina soldadoensis / Globanomalina pseudomenardii Subzone (P4c), 3) at the upper two third of the Morozvella velascoenis P5 Biozone and 4) at the Paleocene/Eocene boundary of Morozovella velascoensis / Morozovella aragonensis - Morozovelia subbotinae (P5/E5), where the P/E boundary is marked by major hiatus. The essential indicators of dissolution within the four intervals samples are low P/B ratios, high relative abundance of the agglutinated taxa, high relative abundance of calcareous taxa resistant to dissolution, especially Lenticulin, Cibicidoides and Anomalinoides and low relative abundance of susceptible calcareous taxa, such as unilocular, uniserial and biserial taxa for the benthics and non-muricate taxa for the planktonic, associated with the high percentage of organic carbon. The probably factors may contribute to the dissolution of planktonic foraminiferal tests in the four intervals of dissolution at the Farafra Oasis is that acidity produced by the degradation of organic matter promotes dissolution in sediment pore waters. Graphical abstract: Highlights: There are four intervals of foraminiferal tests dissolution within the Paleocene of the Farafra Oasis. These intervals characterize by high abundance of agglutinated forms and resistant dissolution taxa as Lenticulin. The probably factor of the dissolution is that acidity produced by organic matter.